KORELASI PRESTASI BELAJAR DAN MOTIVASI BELAJAR MATA PELAJARAN PRODUK KREATIF DAN KEWIRAUSAHAAN DENGAN MINAT BERWIRAUSAHA SISWA SMK TAMANSISWA JETIS YOGYAKARTA TAHUN PELAJARAN 2021/2022 - Jimmy Desduna Ray Mirza; Suparmin; samsul hadi (Universitas Sarjanawiyata Tamansiswa Yogyakarta, 2025)
The goal of this study was to ascertain the relationship between class XI students at SMKTamansiswa Jetis Yogyakarta's learning achievement of creative goods and entrepreneurship as well aslearning motivation partially and concurrently with their interest in entrepreneurship. Ex-post factoresearch is the type used in this study. Using a questionnaire to gauge students' desire for learning,interest in entrepreneurship, and knowledge of creative products and entrepreneurship topics are somemethods of data collecting. A questionnaire is the research's primary tool. Multiple regression analysiswas employed in the data analysis technique to test the first hypothesis, and partial correlation tests wereperformed to test the second and third hypotheses. The findings revealed that (1) there was an associationbetween the creation of creative products and entrepreneurship, as well as between learning motivationand interest in entrepreneurship, with a value of F = 43,047 and a significance value of 0.000 0.05. (2)The achievement of innovative and entrepreneurial products and interest in entrepreneurship arepositively and significantly correlated, with a correlation coefficient value of r count = 0.372 > rtable =0.276 and a significant level of 0.008 0.05. (3) With a coefficient of r count = 0.706 > rtable = 0.276 anda significance level of 0.000 0.05, there is a substantial and positive association between learningmotivation and interest in entrepreneurship.